Can The Conflicts in The Middle East Influence The Election Outcomes in Europe? The European Refugee Crisis in 2015 And Croatia - Picula, Boško (JASSP, 2022)
Seven years before ongoing Ukrainian refugee crisis, the Croatian politics and parliamentary election in 2015 was met by the Middle East refugee crisis. The former Government, despite organizational difficulties, helped an increasing number of migrants to continue their trip to their destinations in Western Europe. Most of the Croatian public supported the decisions by the former Government when it came to a peaceful resolution. The issue of the migrants who pass through Croatia, as well as the relation of Croatia with its neighbouring countries, were among the crucial topics of the election and helped the former unpopular government to avoid a heavier defeat. Croatia itself during the war in the early 1990s took care of hundreds of thousands of refugees, some of them from parts of Croatia and some from the neighbouring Bosnia and Herzegovina. Since the beginning of the refugee crisis with migrants from the Middle East, almost 650,000 people passed through Croatia. This issue (a) crucially influenced the election outcome and the policies of the government and the opposition in Croatia; and (b) showed the strong linkage between conflicts and regional implications in neighbouring parts of the world (the Middle East and South-East Europe).